Surface modification of siloxane containing polyurethane polymer by dielectric barrier discharge at atmospheric pressure - Kostov, K. G. [UNESP]; dos Santos, A. L. R. [UNESP]; Nascente, P. A. P.; Kayama, M. E. [UNESP]; Mota, Rogério Pinto [UNESP]; Algatti, M. A. [UNESP] (Wiley-Blackwell, 2012)
Surface treatment of polymers by discharge plasmas is of great and increasing industrial application because it can uniformly modify the surface of treated samples without changing the material bulk properties. Present work deals with surface modification of siloxane-containing polyurethane (PU-Si) by air dielectric barrier discharge (DBD) at atmospheric pressure. Material characterization was carried out by contact angle measurements, atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS). The surface energy of the polymer surface was calculated from contact angle data using Owens-Wendt-Kaeble method. The plasma-induced chemical modifications are associated with incorporation of polar oxygen containing groups on the polymer surface. The AFM analysis of DBD-treated samples revealed that the surface roughness decreased with increasing the time of treatment. Because of the plasma exposure the surface of DBD-treated polymers became hydrophilic resulting in enhanced adhesion properties. Aging behavior of the treated samples revealed that all polymer surfaces were prone to hydrophobic recovery; however, they did not completely recover their original hydrophobic characteristics. (C) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: dielectric barrier discharge; surface modification; polyurethane; wettability